Citra Tubuh, Pendidikan Ibu, Pendapatan Keluarga, Pengetahuan Gizi, Perilaku Makan dan Asupan Zat Besi pada Siswi SMA - Santi Dwi Rahayu; Fillah Fithra Dieny (MEDIA MEDIKA INDONESIANA, 2012)
The body image, mother’s education, family income, nutritional knowledge, eating behavior and iron intake among senior high school female studentsBackground: The concept of ideal body shape in female adolescent is tall and slim that oftenly to lead restriction of the food intake especially the food sources of iron that are considered as foods with high fat. This study aimed to identify factors association between body image, mother’s education, family income, nutritional knowledge, and eating behavior with iron intake among senior high school female students.Method: This study used cross sectional design, and it was conducted on female students at SMA Negeri 1 Tangerang Selatan. The selection of 80 subjects was performed by stratified random sampling technique. Data on body image was obtained by body shape questionnaire, family income, mother’s education, nutritional knowledge and eating behavior were collected by questionnaire, and iron intake was obtained by 24-hour food recall. Data were analyzed by Rank Spearman.Result: Subjects aged in 15-17 years old. The subjects had a dissatisfaction of their body image were 41.25% subjects and 40% subjects had deficit iron intake. Subjects had inappropriate eating behavior 47.5% and 66.3% were classified as intermediate level of family income. The level of mother’s education at SMA/MA were 53.8% subjects and only 7.5% subjects had good nutritional knowledge. The subjects had a dissatisfaction of their body image would be had inappropriate eating behavior so they had lower iron intake too. The good mother’s education of subjects would be had good iron intake, moreover the higher family income that increased food expenditure so subjects had adequate iron intake. The nutritional knowledge was not correlated with iron intake.Conclusion: Body image was associated with eating behavior. Eating behavior, mother’s education, and family income were correlated with iron intake.Keywords: Body image, eating behavior, iron intake ABSTRAKLatar belakang: Konsep tubuh ideal tinggi langsing menimbulkan remaja putri melakukan pembatasan asupan makanan terhadap sumber zat besi yang dianggap sebagai makanan dengan lemak tinggi. Tujuan penelitian untuk mengidentifikasi hubungan antara  citra tubuh, pendidikan ibu, pendapatan keluarga, pengetahuan gizi dan perilaku makan dengan asupan zat besi pada siswi SMA.Metode: Rancangan penelitian cross sectional. Populasi adalah siswi SMA Negeri 1 Tangerang Selatan. Pemilihan 80 subyek dilakukan secara stratified random sampling. Data citra tubuh dengan body shape questionnaire, pendapatan keluarga dengan angket, pendidikan ibu, pengetahuan gizi dan perilaku makan dengan kuesioner serta asupan zat besi dengan kuesioner food recall 24 jam. Data dianalisis dengan korelasi Rank Spearman.Hasil: Subyek berusia 15-17 tahun. Subyek dengan ketidakpuasan citra tubuh sebanyak 41,25% dan 40% subyek mempunyai tingkat asupan zat besi defisit. Subyek dengan perilaku makan tidak sesuai sebanyak 47,5% dan 66,3% subyek mempunyai tingkat pendapatan keluarga ekonomi menengah. Tingkat pendidikan ibu subyek tamat SMA/MA sebanyak 53,8% dan hanya 7,5% yang mempunyai tingkat pengetahuan gizi baik. Subyek dengan citra tubuh yang tidak puas cenderung mempunyai perilaku makan yang tidak sesuai sehingga asupan zat besinya rendah. Subyek dengan ibu berlatar belakang pendidikan tinggi cenderung mempunyai asupan zat besi baik, selain itu makin tinggi pendapatan keluarga, maka pengeluaran belanja pangan makin meningkat sehingga asupan zat besi pada subyek terpenuhi. Namun pengetahuan gizi tidak berhubungan dengan perilaku makan.Simpulan: Citra tubuh berhubungan dengan perilaku makan. Perilaku makan, pendidikan ibu, dan pendapatan keluarga berhubungan dengan asupan zat besi